2023
DOI: 10.1111/fcp.12934
|View full text |Cite
|
Sign up to set email alerts
|

Novel ginsenoside monomer RT4 promotes colitis repair in mice by regulating miR‐144‐3p/SLC7A11 signaling pathway

Abstract: BackgroundGinsenoside RT4 (RT4) is a new biologically active compound extracted from ginseng that possesses numerous medicinal and pharmacological properties. However, its potential therapeutic effect of ginsenoside RT4 on ulcerative colitis remains unknown.Methods and resultsIn this study, we investigated the anti‐inflammatory effects of ginsenoside RT4 and its underlying molecular mechanism in the treatment of ulcerative colitis mice induced with dextran sulfate sodium (DSS). Our results demonstrate that gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The highly specific distribution of intestinal inflammation sites, as well as mucosal healing, are particularly important treatment strategies. RT4 (a natural product) showed positive anti-inflammatory effects in LPS-induced RAW 264.7 cells and in DSSinduced UC mice (intraperitoneal injected with RT4) [20]. However, oral administration is more suitable for treating ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highly specific distribution of intestinal inflammation sites, as well as mucosal healing, are particularly important treatment strategies. RT4 (a natural product) showed positive anti-inflammatory effects in LPS-induced RAW 264.7 cells and in DSSinduced UC mice (intraperitoneal injected with RT4) [20]. However, oral administration is more suitable for treating ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that RT4 shows both a hepatocytoprotective effect [17] and an anti-inflammatory effect [18,19]. It is worth mentioning that intraperitoneal injections of RT4 have the potential to alleviate disease symptoms, increase colon length and weight, and improve the pathological state of colonic tissues in UC mice [20]. It has further been revealed that RT4 could downregulate the levels of pro-inflammatory cytokines (IL-1β, TNF-α) and up-regulate the level of anti-inflammatory cytokines (IL-10) in the colonic tissue of UC mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation